Regionalization of a conceptual rainfall-runoff model based on similarity of the flow duration curve: a case study from the semi-arid Karkheh Basin, Iran - Masih, Ilyas; Uhlenbrock, Silke; Maskey, S.; Ahmad, M.D. (Elsevier, 2010)
The study examines the possibility of simulating time series of streamflows for poorly gauged catchments based on hydrological similarity. The data of 11 gauged catchments (475-2522 km2), located in the mountainous semi-arid Karkheh river basin of Iran, is used to develop the procedure. The well-known HBV model is applied to simulate daily streamflow with parameters transferred from gauged catchment counterparts. Hydrological similarity is defined based on four similarity measures: drainage area, spatial proximity, catchment characteristics and flow duration curve (FDC). The study shows that transferring HBV model parameters based on the FDC similarity criterion produces better runoff simulation compared to the other three methods. Furthermore, it is demonstrated that the FDC based regionalization of HBV model parameters works reasonably well for streamflow simulations in the data limited catchments in the mountainous parts of the Karkheh river basin. In addition, it could be demonstrated that the parameter uncertainty of the model has little impact on the FDC based regionalization approach. The methodology presented in this paper is easy to replicate in other river basins of the world, particularly those facing decline in streamflow monitoring networks and with a limited number of gauged catchments.